ANALISIS SIFAT TERMAL DAN UJI KELARUTAN DARI KARET ALAM SIKLIS DAN KARET ALAM CAIR SIKLIS - Leni Widiarti; Basuki Wirjosentono; Eddyanto Eddyanto (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2018)
Abstract. The research has done analysis of thermal properties and solubility test of Cyclic Natural Rubber (CNR) and Cyclic Liquid Natural Rubber (CLNR). Cyclic Liquid Natural Rubber (CLNR) is a cyclical natural rubber which has decreased molecular weight. Synthesis of Cyclic Liquid Natural Rubber (CLNR) do by oxidative degradation after cyclic. Oxidative degradation after cyclic using Cyclic Natural Rubber (CNR) and phenylhydrazine reagent with flow rate 2 LMin-1 of oxygen atmosphere during 24 hours. Thermal analysis of Cyclic Natural Rubber (CNR) and Cyclic Liquid Natural Rubber (CLNR) by Differential Scanning Calorimetry (DSC),the glass transition temperature (Tg) of Cyclic Natural Rubber (CNR) and Cyclic Liquid Natural Rubber (CLNR) are 102,82 o C and 103,67 o C, the crystal transition temperature (Tc) of Cyclic Natural Rubber (CNR) and Cyclic Liquid Natural Rubber (CLNR) are 362,45 o C and 330,29 o C and the melting transition temperature ( Tm) of Cyclic Natural Rubber (CNR) and Cyclic Liquid Natural Rubber (CLNR) are 509,24 o C and 440,00 o C. Solubility test by dilute Cyclic Natural Rubber (CNR) and Cyclic Liquid Natural Rubber (CLNR) in some solvent with different properties and polarity index. Solubility test shows the results Cyclic Natural Rubber (CNR) and Cyclic Liquid Natural Rubber (CLNR) has polarity index around 2,4 – 4,4 and 2,4 and 4,4. Keywords: CLNR, CNR, oxidative degradation